Security Management in the Field of Critical Infrastructure Protection in the Republic of Serbia - State and Perspectives - Stajić, Ljubomir; Mirković, Vladan M; Radivojević, Nenad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Term „critical infrastructure” became part of the post-Cold War security discourse when the first legal and political acts, containing this term, emerged. The Law on Critical Infrastructure in the Republic of Serbia was adopted in 2018, and some of the most important issues regulated by the Law are the competences and responsibilities of entities in the critical infrastructure protection system. The subject of our research was security management in the field of critical infrastructure protection. As a result of the research in the paper: 1. Levels, types and competencies of security management in the field of critical infrastructure protection have been identified; 2. Their mutual relationship has been determined and 3. Recommendations of measures and solutions that need to be taken in order to establish an integrated protection system in this area have been given.